1990
DOI: 10.1042/bj2670467
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic uptake and metabolic disposition of leukotriene B4 in rats

Abstract: 1. In isolated perfused rat liver and in vivo, up to 25 % of [3H]leukotriene B4 was eliminated from the circulation via hepatic uptake and biliary excretion within 1 h. Total body recovery of 3H amounted to about 60 % of infused [3H]leukotriene B4. 2. Hepatobiliary excretion of leukotriene B4 and its metabolites exceeded renal elimination by about 4-fold and depended, in contrast with excretion of cysteinyl leukotriene E4, upon continuous taurocholate supply. 3. Analyses of bile, liver and recirculated perfusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…When rats were injected with radiolabeled LTB 4 , both bile and urine were found to contain metabolites. The bile contained 20 -25% of the injected radioactivity, whereas the urine contained less than 10% of the injected dose (33). Reversed phase HPLC analysis of the bile and urine revealed that most metabolites were less lipophilic than LTB 4 ; however, structural identification of these metabolites was not reported.…”
Section: Discussionmentioning
confidence: 92%
“…When rats were injected with radiolabeled LTB 4 , both bile and urine were found to contain metabolites. The bile contained 20 -25% of the injected radioactivity, whereas the urine contained less than 10% of the injected dose (33). Reversed phase HPLC analysis of the bile and urine revealed that most metabolites were less lipophilic than LTB 4 ; however, structural identification of these metabolites was not reported.…”
Section: Discussionmentioning
confidence: 92%
“…Although leukocytes, especially neutrophils, are known to efficiently catalyze the degradation and inactivation of LTB 4 , the role of the liver would also be of major importance, since this tissue is also responsible for the elimination of LA and AA metabolites released into systemic circulation (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that metabolism in the liver and kidney may be important in the regulation of LTB4 levels in vivo. Accordingly, evaluation of the metabolic disposition of LTB4 in vivo confirmed extensive P-oxidation of LTB4 in the monkey and the rabbit (Serafin et al, 1984) and intrahepatic a-oxidation followed by Poxidation from the Q-end in the rat (Hagmann & Korte, 1990), leading mainly to the production of volatile derivatives, with no intact LTB4 detected in the bile or the urine. In the present study, we provide a detailed kinetic analysis of LTB4 in conscious rabbits after single i.v.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies on the metabolism of LTB4 in vitro and in vivo (Harper et al, 1986;Hagmann & Korte, 1990) have suggested that 0-and P-oxidation-resistant analogues of LTB4 might be protected from rapid degradation in vivo. Our results show that, despite its in vitro a-oxidation resistant property (Tanaka et al, 1988), 20-F3-LTB4 is rapidly and efficiently removed from the circulation after a single i.v.…”
Section: Disposition Of Ltb4 Analoguesmentioning
confidence: 98%